Why Do South African Companies Adopt the UN Sustainable Development Goals? - Pinheiro, Alan Bandeira; de Oliveira Silva Ramalho, Ana Lidia; de Lima Bernardo, Eduardo Becher; do Prado, Nágela Bianca (Organizations and Markets in Emerging Economies, 2026)
Several previous studies have highlighted that the adoption of sustainable development goals in South Africa has contributed to poverty reduction, increased literacy rates, and progress in the fight against HIV. The purpose of this study is to understand the motivations underlying South African companies’ adoption of the UN Sustainable Development Goals and to assess the implications of this decision. To this end, the adoption of SDGs by 116 South African companies, focusing on board composition—specifically board size, diversity, skills, tenure, and independence—as antecedents, and corporate reputation as an outcome were analyzed. To analyze the data, we employed a mixed-methods approach, utilizing both multivariate analysis and fuzzy-set Qualitative Comparative Analysis (fsQCA). Both symmetric (multivariate analysis) and asymmetric (fsQCA) analyses provide strong evidence that three key board characteristics (gender diversity, board skills, and board independence) significantly influence the adoption of the SDGs. Additionally, the findings demonstrate that SDG adoption contributes to enhanced corporate social reputation. The findings have implications for both Agency Theory and Stakeholder Theory.
Keywords: Sustainable Development Goals; Corporate Reputation; Emerging economies; board composition; agency theory; stakeholder theory; mixed-methods approach